The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.jff.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Lingonberry juice improves endothelium-dependent vasodilatation of mesenteric arteries in spontaneously hypertensive rats in a long-term intervention

Abstract: Experimental hypertension Vasodilatation Polyphenols Nitric oxide EDHF A B S T R A C T Phenolic compounds of berries, fruits and vegetables affect vascular health. Endotheliumdependent vasodilatation has an important role in blood pressure development by controlling the vascular tone. Endothelial cells produce and release various relaxing and contracting factors, like nitric oxide (NO), cyclo-oxygenase (COX)-derived prostanoids and endothelium-derived hyperpolarizing factor (EDHF). The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…The data indicate that the leaf extract induced a pronounced endothelium-dependent relaxation involving NO and also to some extent vasorelaxant prostanoids. These observations are in agreement with previous ones showing that several polyphenol-rich sources (i.e; lingonberries [27] and red wine [26]) induced redox-sensitive endothelium-dependent relaxations mostly involving the formation of NO-and, often also, to some extent, EDH.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The data indicate that the leaf extract induced a pronounced endothelium-dependent relaxation involving NO and also to some extent vasorelaxant prostanoids. These observations are in agreement with previous ones showing that several polyphenol-rich sources (i.e; lingonberries [27] and red wine [26]) induced redox-sensitive endothelium-dependent relaxations mostly involving the formation of NO-and, often also, to some extent, EDH.…”
Section: Discussionsupporting
confidence: 93%
“…Several sources of polyphenols including red wines [26], grape juices, berry juices [27] and fruits such as acaí [28] have a potential to improve vascular health by various mechanisms including the induction of vasodi- reporting the content of various phenolic compounds [22] and the antioxidant capacity of extracts using three methods (TEAC, DPPH and ORAC assays, [14]). A correlation has been made between these results and the endothelium-dependent vasorelaxation results at 0.1 mg/mL of extract.…”
Section: Discussionmentioning
confidence: 99%
“…All three kinds of fruit were rich in polyphenols. It could be concluded that endothelium-dependent vasodilatation of spontaneously hypertensive rats could be improved by long-term lingonberry juice treatment [85]. In another study, cranberry juice, which was rich in polyphenols, was investigated and no significant change caused by cranberry juice on peripheral endothelial function was found during the study [86].…”
Section: Mechanisms Of Action Of Juice On Cardiovascular Diseasesmentioning
confidence: 99%
“…In Kivimäki and coauthors` previous study it is shown that lingonberry juice enhanced endothelium-dependent vascular relaxation in spontaneously hypertensive rats (SHR) (Kivimäki et al, 2011). It is suggested that blood pressure -lowering effect of polyphenol-rich foods is partly due to inhibition of angiotensin-converting enzyme (ACE), which is a key regulator of blood pressure (Actis-Goretta et al, 2006; Persson et al, 2011).…”
Section: Resultsmentioning
confidence: 99%